2022
DOI: 10.3390/su14094942
|View full text |Cite
|
Sign up to set email alerts
|

Ambient and Heat-Cured Geopolymer Composites: Mix Design Optimization and Life Cycle Assessment

Abstract: The feasibility of producing sustainable cement-free composites and its environmental impact were investigated in this research. Experimental parametric evaluation was carried out in this regard to explore the optimum mix design of the composites. The effect of synthesis parameters and curing conditions on the behavior of the produced geopolymer composites was investigated. The studied parameters included the molarity of the sodium hydroxide solution (12 M, 14 M, and 16 M), the sodium silicate to sodium hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…Our results suggest that ambient temperature air curing is the most suitable curing condition for achieving the highest mechanical strengths (compressive, tensile and flexural) and extended longevity of the bacteria incorporated geo-polymeric mortars. Rabie et al [32] have investigated the feasibility of producing sustainable cement-free composites and its environmental impact, which corroborates with our experimental results. High temperature air curing (90 o C heat curing for 72 h) also showed good performance on mechanical strengths and durability of the bacterium incorporated geo-polymeric materials (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that ambient temperature air curing is the most suitable curing condition for achieving the highest mechanical strengths (compressive, tensile and flexural) and extended longevity of the bacteria incorporated geo-polymeric mortars. Rabie et al [32] have investigated the feasibility of producing sustainable cement-free composites and its environmental impact, which corroborates with our experimental results. High temperature air curing (90 o C heat curing for 72 h) also showed good performance on mechanical strengths and durability of the bacterium incorporated geo-polymeric materials (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…The curing conditions included ambient curing of specimens with age, according to results found in Ref. [ 23 ], and the composites obtained are described in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Ref. [ 147 ] studied the performance of ambient and heat-cured geopolymer composites. They found that 1-day heat cured geopolymer mortar gained more than twice the compressive strength of 28 days ambient cured geopolymer mortar.…”
Section: Impact Of Curingmentioning
confidence: 99%
“…The production of geopolymer mortar is more environmentally friendly compared to OPC mortar. For example, Figure 18 shows that 1 m 3 of geopolymer mortar produces 72% GWP, 65% AP, 41% EP, and 29% ADP less than the production of 1 m 3 of OPC [ 147 ]. The main processes studied were the extraction of source materials, transportation of the material, and the production of the final product.…”
Section: Cost–benefitmentioning
confidence: 99%